Students' attitudes towards research: Applying best practice principles through a student-centred approach - Belgrave, Korah L.; Jules, Janice E. (My University, 2015)
Informal observation over the last five years reveals that a number of students in the undergraduate programme in Linguistics at The University of the West Indies (UWI) Cave Hill Campus demonstrate negative attitudes towards courses that require them to learn and participate in the research process. Hence, this paper presents an analysis of the attitudes of undergraduate linguistics students at the Cave Hill Campus towards research in order to determine students' perception of the use of student-centred principles associated with best practices during instruction in the courses with research activities: LING2302: Sociolinguistics, LING3202: Creole Linguistics, and LING2099: Research Methods in Linguistics, and the implications of these findings for the teaching/learning process. Through an action research design, information was collected from a purposive sample comprising Level 2 and 3 students in the linguistics undergraduate programme. Accordingly, qualitative data gathered from a questionnaire and from a focus group provide a description of students' orientation towards research. There is also analysis of students' perceptions of the extent to which the course content addresses their research needs and caters to their success in life beyond the classroom. A quantitative component provides some measurement of the dependent variable. The analysis of the results validate the hypothesis that students' perceptions of the functionality of research and its meaningful application to real-life situations results in a positive attitude towards research. Findings suggest that greater focus on student-centred principles of best practice in the courses' research components would enhance the worth and usefulness within a broader world context.g is an element of best practice that can be explored as a means of improving teaching and learning at The UWIOC.
Paper presented at the Regional Conference on Institutionalising Best Practice in Higher Education, UWI, St. Augustine, Trinidad and Tobago, 24-26 June, 2015.
Keywords: Undergraduate students; Linguistics; Best practices; Research; Student attitudes; Action research; The University of the West Indies, Cave Hill